Microwave-assisted extraction of cellulose nanocrystals from almond (Prunus amygdalus) shell waste - Valdés, Arantzazu; Mondragon, Gurutz; Garrigós, María Carmen; Eceiza, Arantxa; Jiménez, Alfonso (Frontiers in Nutrition, 2023)
Almond (Prunus amygdalus) is one of the most common tree nuts on a worldwide basis. This nut is highly regarded in the food and cosmetic industries. However, for all these applications, almonds are used without their shell protection which is industrially removed contributing around 35−75 % of the total fruit weight. This residue is normally incinerated or dumped causing several environmental problems. In this work, a novel cellulose nanocrystals (CNCs) extraction procedure from almond shell (AS) waste by using microwave-assisted extraction was developed and compared with the conventional approach. A three-factor, three-level Box-Behnken design with five central points was used to evaluate the influence of extraction temperature, irradiation time and NaOH concentration during the alkalization stage in crystallinity index (CI) values. A similar CI value (55.9 ± 0.7 %) was obtained for the MAE process, comprising only 3 stages, compared to the conventional optimized procedure (55.5± 1.0 %) with 5 stages. As a result, a greener and more environmentally friendly CNCs extraction protocol was developed with a reduction of time, solvent and energy consumption. FTIR spectra, XRD diffractograms, AFM and SEM images, and thermal stability studies of samples confirmed the removal of non-cellulosic components after the chemical treatments. TEM images revealed a spherical shape of CNCs with average size of 21 ± 6 nm, showing great potential to be used in food packaging, biological, medical and photoelectric materials. This study successfully applied MAE for the extraction of spherical-shaped CNCs from AS with several advantages compared to the conventional procedure, reducing costs for industry.